2022
DOI: 10.3390/agriculture12070942
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Larger-Sized Fish on Water Quality, Growth Performance, and the Economic Yield of Nile Tilapia (Oreochromis niloticus L.) in Floating Cages

Abstract: Earlier research has mostly focused on the impacts of stocking density on fish growth, yield, and survival rate; however, knowledge of the effects of stocking larger-sized fish, particularly Nile Tilapia, is lacking. This type of research is critically important for increasing food security, achieving sustainable goals, and facing the challenges of climate change in the near future. Therefore, we investigated the effects of initial stocking body sizes of Nile Tilapia (Oreochromis niloticus) on water quality, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
11
2
1
Order By: Relevance
“…Low FCR significantly reduces the operating cost as feed is one of the major costs for fish culture. In addition, the economics of carp culture can also be determined by fish size, the bigger the fish, the greater the price is [36]. Contrastingly, the net benefit was reported higher at over stocking density of Pangasius bocourti [48] and Clarias gariepinus [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low FCR significantly reduces the operating cost as feed is one of the major costs for fish culture. In addition, the economics of carp culture can also be determined by fish size, the bigger the fish, the greater the price is [36]. Contrastingly, the net benefit was reported higher at over stocking density of Pangasius bocourti [48] and Clarias gariepinus [6].…”
Section: Discussionmentioning
confidence: 99%
“…Prices of inputs and fish resembled to wholesale market prices in 2019 of Noakhali, Bangladesh. Net return (R), return on investment (ROI), and cost-benefit ratio (CBR) were reckoned following Shamsuddin et al [36] as: R = I -(FC + VC) (6) where R refers to net return; I is income from fish sold; FC and VC stand for fixed cost and variable cost, respectively. ROI = N I TC × 100 (7) where NI refers to net income and TC is total cost BCR = Total net return Total input cost (8) when the BCR is > 1.0, the project is anticipated to have a positive net present value; when it is < 1.0, the project's expenses outweigh its benefits [36].…”
Section: Economics Of Carp Culturementioning
confidence: 99%
“…En ese sentido la instalación de una granja piscícola dedicada a la producción de Tilapia es viable en términos económicos, ya que la demanda constituye una oportunidad para generar un posicionamiento con la proyección antes descrita (Philip Kotler y Gary Armstrong, Prentice Hall, 2003;Fino Arboleda, 2014;USDA. 2005;Stanton 2004) Respecto a la viabilidad técnico ambiental (Henry-Silva et al, 2022;Souza et al, 2022;Arechavala et al, 2022) , al tomar los valores para establecer las condiciones climatológicas favorables para la instalación de la granja (Ragasa et al, 2022;Zappernick et al, 2022;Shamsuddin et al, 2022;Datta & Kumar, 2022), se encontró una temperatura de 24°C recurrente en los cuerpos de agua con unos recursos hídricos constantes, PH en rangos óptimos (6.5-7.5), oxígeno disuelto de 4-7 mg/l y saturación de oxígeno del 86%, estaciones bien marcadas en la zona del sauce (estación seca va de diciembre-abril y la estación lluviosa de mayo-noviembre) y el posicionamiento geográfico son favorable para la instalación de una granja piscícola, acompañado por políticas económicas benefactoras para la realización de actividades productivas como la piscicultura ya que instituciones de gobierno como el MEFFCA están incentivando el cultivo de Oreochromis niloticus para consumo familiar como también para su comercialización (Martínez et al, 2015;FAO. 2017;FAO 2020;FAO 2019).…”
Section: Autoría Propiaunclassified
“…The growth rates changed depending on stocking density, which was also reported by Begum (2009), Rubel (2008), andMasum (2011). Abaho et al (2020) and Shamsuddin et al (2022) found that the growth rate of Nile tilapia (Oreochromis niloticus) was affected by different stocking densities.…”
Section: Growthmentioning
confidence: 99%
“…The effect of stocking density on production of Nile tilapia (Oreochromis niloticus) was studied by Abaho et al (2020) and Shamsuddin et al (2022). CONCLUSION Stocking density is an important parameter in fish culture as it has a direct effect on the growth and production of fish.…”
Section: Productionmentioning
confidence: 99%